Analysis of the Influence of the Use of Social Media Instagram, Business Location, and Destination Image on Interest in Revisiting the Karo Strawberry Garden - Nur Aisyah Nasution; Sri Indayani; Jeihan Vanindah (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyze the influence of the use of Instagram social media, business location, and destination image on the interest in visiting Karo Strawberry Garden again. Along with the development of experiential tourism, the use of social media is one of the important factors in attracting visitors, especially for natural tourist destinations such as strawberry farms. This study uses quantitative methods with multiple linear regression approaches to measure how much influence each independent variable has on return visit interest. The results showed that all three variables - Instagram usage, business location, and destination image - had a significant effect on return visit interest. Of the three variables, destination image has the most dominant influence in shaping visitors' interest in returning, followed by business location, and finally, the use of Instagram social media. This indicates that while promotion through social media plays an important role in attracting initial visits, adequate in-person experience at the destination determines interest in repeat visits more. Thus, the management of Karo Strawberry Farm is advised to focus more on improving the destination image through the quality of facilities, services, and overall experience, as well as supporting social media promotion and location accessibility as supporting factors.